Knowledge and fostering of the female condom by professionals of the STD/HIV reference units of Fortaleza-CE: the female condom needs to get out of the shop windows - Oliveira, Nancy da Silva; Moura, Escolástica Rejane Ferreira; Guedes, Tatiane Gomes; Almeida, Paulo César de (Saúde e Sociedade, 2008)
This exploratory-descriptive study took place in the 10 public reference institutions for treating sexually transmitted diseases in the city of Fortaleza, state of Ceará. The goal was to identify the doctors' and nurses' knowledge related to the female condom; to investigate the way these professionals foster its use; and also to investigate the association between knowing how to use the female condom and the variables profession and sex. Twenty-six of the 57 professionals took part in the project. The sample is made up of 11 doctors and 15 nurses who were present in the institutions during the period of data collection and who freely accepted to take part in this study. The data were collected through a questionnaire from January to March 2006. They were organized in tables that contain only the absolute figures, as the sample is small. Fisher and Fisher-Reeman-Halton tests were carried out in order to investigate the existence of association between variables. The professionals, independently of the category, presented little knowledge related to the basic characteristics of the method and how to fit it (Fisher's p values above 10%). However, there was an association between knowing the steps to fit the female condom and feminine sex (p = 0.034). Those professionals hardly foster the implementation of this condom. They attributed this fact to the high price, to the fact that the unit does not offer it, to the belief that women do not know about it or will not use it, and to the fact that the male condom is much more used and easier to get. Those reasons should be banned from the professionals' discourse.